1982
DOI: 10.3382/ps.0610288
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Salmonella Species and Serotypes in Young Whole Chicken Carcasses in 1979 as Compared with 1967

Abstract: A survey was conducted to determine the incidence of salmonellae in processed, ready-to-market, whole young chickens. Carcasses from 15 federally inspected chickens eviscerating plants were analyzed using a carcass washing technique for determining the presence of salmonellae. The results obtained during the 1979 incidence survey were compared to results obtained in an identical 1967 Salmonella survey. In the 1967 study, salmonellae were isolated from 171 ot the 597 (28.6%) whole chickens tetrathionate broth r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

1987
1987
1996
1996

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 8 publications
1
8
1
Order By: Relevance
“…Copenhagen, and S. derby are three serotypes frequendy incriminated in outbreaks of human salmonellosis and are among the species commonly isolated from livestock (Pocurull et al, 1971;Green et al, 1982;Kirby, 1985;Murray, 1987); yet, the same three serotypes were isolated at an unexpectedly low frequency in the present study, with only one culture for each of the three serotypes being identified.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Copenhagen, and S. derby are three serotypes frequendy incriminated in outbreaks of human salmonellosis and are among the species commonly isolated from livestock (Pocurull et al, 1971;Green et al, 1982;Kirby, 1985;Murray, 1987); yet, the same three serotypes were isolated at an unexpectedly low frequency in the present study, with only one culture for each of the three serotypes being identified.…”
Section: Discussioncontrasting
confidence: 48%
“…Rengel and Mendoza (1984) found Salmonella anatum, Salmonella bloemfontein, and Salmonella schwarzengrund most often among the 373 isolates of Salmonella representing 11 different serotypes isolated from carcasses in Venezuela. Green et al (1982) examined carcasses from 15 federally inspected processing plants in 1979, 10 of which had been examined in 1967. Comparison between the two surveys, in which similar methodology was used, revealed an increase in frequency of Salmonella contamination from 28.6% of the carcasses in 1967 to 36.9% in 1979.…”
Section: Introductionmentioning
confidence: 99%
“…In 1967, an FSIS survey of chicken eviscerating plants showed 28.6% of broilers to be contaminated with Salmonella; a followup survey was conducted in 1979 (Green et al, 1982). These data showed the Salmonella contamination rate in broilers to be 36.9%.…”
Section: Introductionmentioning
confidence: 94%
“…A study completed in 1979 (Green et al, 1982) showed 36.9% of chickens to be contaminated. But although the data on Salmonella contamination do not represent a new finding, media treatment of the issue, such as the "60 Minutes" television presentation in March 1987, did much to reinforce the public impression that Salmonella contamination of poultry is a new phenomenon and somehow related to a departure from traditional processing and inspection.…”
Section: Introductionmentioning
confidence: 98%
“…, , " , " , (Todd, 1980;Green et al, 1982). Efforts to Incidence of Salmonella on eviscerated reduce ^ ad of Salmondla at various poultry carcasses is frequent and the sta ges of production and processing in the poultry industry have had only limited success.…”
Section: Introductionmentioning
confidence: 98%